Association between Food Behaviour of Pregnant Women and Status of Serum Vitamin B12 and Neonatal Outcome – A Cross-Sectional Study (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: To find the association between serum vitamin B12 and food behavior of the pregnant women and its influence on perinatal outcome.Methods: This cross-sectional study was conducted in the Department of Obstetrics & Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka between June 2012 to July 2013. A total of 102 uncomplicated pregnant women attending at the Obstetrics & Gynaecology Department of BSMMU, Dhaka were the study population. Plasma vitamin B12 was measured by Abbott Axsym System using a Enzyme Immuno Assay Technique with the blood collected in a plain test tube. A serum vitamin B12 level of < 200 pg/mL was considered as low serum vitamin B12 level. The outcome variables were birth weight, small-for-date, neural tube defects and other congenital malformations.Result: The selected pregnant women were housewife (74.5%) from low socioeconomic strata. They were generally urban resident (90.2%) with mean age being 26.4 years. In terms of education 17.6% were primary level, 30.4% SSC level, 31.4% HSC level and 20.6% graduate and higher level educated. Majority (90.2%) was urban resident with average monthly family income being Taka 29460. One-third (33.3%) was overweight and 6.9% obese. Two-thirds (66.7%) were at 37-39 weeks of gestation and nullipara. More than 60% received ANC (antenatal care) aregularly. Over one-third (35.3%) had low serum vitamin B12 (< 200 pg/mL). The food behaviour of the women was found to be associated with vitamin B12 deficiency. The pregnant women with low serum vitamin B12 (< 200 pg/ml) had significantly lower weekly consumption of fishes and eggs which are the rich source of vitamin B12. The weekly fish, eggs and amount of milk consumed by the pregnant women with low serum vitamin B12 were much lower than those consumed by the pregnant women with normal serum vitamin B12. The pregnant women with low serum vitamin B12 were more likely to carry a higher risk of adverse perinatal outcome. The incidences of low-birth weight and small-for-dates were staggeringly higher in women with low serum vitamin B12 (33.3% and 27.8% respectively) compared to those in women with normal serum vitamin B12.Conclusion: The study concluded that pregnant women with low serum vitamin B12 are accustomed to taking low fish and eggs in their daily diet compared to those who have normal serum vitamin B12. The incidence of low birth weight and small-for-date babies are more prevalent in the pregnant women with subclinical deficiency of vitamin B12.Ibrahim Card Med J 2017; 7 (1&2): 84-91